Evaluation of lysophosphatidic acid in vaginal fluid as a biomarker for ovarian cancer: A pilot study - Minis, Evelyn; Holcomb, Kevin; Sisti, Giovanni; Nasioudis, Dimitrios; Kanninen, Tomi T.; Athanasiou, Aikaterini; Frey, Melissa K.; Chapman-Davis, Eloise; Caputo, Thomas A.; Witkin, Steven S. (European journal of obstetrics & gynecology and reproductive biology: X, 2019)
There remains a need to differentiate between women with a benign or a malignant adnexal mass prior to surgery. As part of an ongoing evaluation of vaginal fluid compounds as potential tumor biomarkers we evaluated whether vaginal lysophosphatidic acid (LPA) predicted the subsequent diagnosis of a malignant adnexal mass. In this prospective pilot study vaginal fluid was obtained from 100 post-menopausal women referred for evaluation of a suspicious adnexal mass and tested for LPA by ELISA. Clinical data and serum CA125 results were obtained only after completion of all laboratory testing. Twenty eight of the women were subsequently diagnosed with an ovarian malignancy, four had a borderline tumor and 68 had a benign diagnosis. Among women with a malignant ovarian mass, 11 (39.3%) had an endometrioid adenocarcinoma +/- Clear cell tumor components, 6 (21.4%) had a high grade serous carcinoma, 3 (10.7%) had a mucinous tumor, 2 each (7.1%) had a malignant mixed mesodermal or a granulosa tumor and 1 each (3.6%) had a Clear cell tumor, a mixed cell tumor, leimyosarcoma or metastatic adrenal tumor. Compared to the median vaginal LPA level in women with benign lesions (1.5 μM), LPA was significantly elevated only in women with endometrioid ovarian cancer (7.9 μM) (p = 0.0137). Of the 6 endometrioid tumors in which values for both plasma CA125 and vaginal LPA were available 5 were positive only for LPA while one was only CA125 positive. Detection of LPA in vaginal secretions may be of value for the noninvasive diagnosis of endometrioid ovarian malignancies in post-menopausal women.